Students’ Perception on Individual Learning versus Cooperative Learning Using Numbered Heads Together (NHT) Method in English Classroom - Tiara Sonita; Desty Febria (Journal of English Education and Teaching, 2022)
In this era, teachers need to choose the proper method in teaching and vice versa; students’ participation in the classroom should be one of biggest concern for the teachers. With the right method, learning activities can be more effective to the students and will also improve their participation. This study intends to use Numbered Heads Together (NHT) as one of cooperative learning method to improve students’ participation in classroom. The methodology that being used is Classroom Action Research (CAR) and the research method is quantitative. The researchers will observe and implement the method by making two exercises in group, then give a self-assessment questionnaire to the students about their opinion to individual activities and group work activities. The results showed that NHT method is successfully improved students’ participation and activeness in the classroom with each of the students recorded to have significant improvement in their participation, while there are pros and cons from the self-assessment about the students’ preferences for each individual and group work activities. There are also advantages and disadvantages from NHT method itself. The disadvantage is no doubt making the student uncomfortable and don’t like to work in group. Further research is suggested to take action to the disadvantage of cooperative learning method.